(untitled) - Elbaum, Sandra N. (Massachusetts, 1985)
Students learn more, remember more, and can use grammar more effectively when they learn language in context. GRAMMAR IN CONTEXT offers comprehensive explanations, culturally rich readings, and numerous practice and writing actitivies.
Keywords: English language,Anh ngữ thực hành; Grammar,Ngữ pháp